Factors related to HPV vaccine uptake and 3-dose completion among women in a low vaccination region of the USA: an observational study. Issue 1 (December 2016) - Wilson, Andrew; Hashibe, Mia; Bodson, Julia; Gren, Lisa; Taylor, Brooke; Greenwood, Jessica; Jackson, Brian; She, Rosemary; Egger, Marlene; Kepka, Deanna
Abstract Background To assess the demographic and attitudinal factors associated with HPV vaccine initiation and completion among 18–26 year old women in Utah. Method Between January 2013 and December 2013, we surveyed 325 women from the University of Utah Community Clinics about their HPV vaccine related beliefs and behaviors. Odds ratios (ORs) were estimated from logistic regression models to identify variables related to HPV vaccine initiation and series completion. Results Of the 325 participants, 204 (62.8 %) had initiated the vaccine and 159 (48.9 %) had completed the 3-dose series. The variables associated with HPV vaccine initiation were lower age (OR = 1.18 per year); being unmarried (OR = 3.62); not practicing organized religion (OR = 2.40); knowing how HPV spreads (OR = 6.29); knowing the connection between HPV and cervical cancer (OR = 3.90); a belief in the importance of preventive vaccination (OR = 2.45 per scale unit); strength of doctor recommendation (OR = 1.86 per scale unit); and whether a doctor's recommendation was influential (OR = 1.70 per scale unit). These variables were also significantly associated with HPV vaccine completion. Conclusion The implications of these findings may help inform policies and interventions focused on increasing HPV vaccination rates among young women. For example, without this information, programs might focus on HPV awareness; however, the results of this study illustrate that awareness is already high (near saturation) in target populations and other factors, such as strong and consistent physician recommendations, are more pivotal in increasing likelihood of vaccination. Additionally, our findings indicate the need for discussions of risk assessment be tailored to the young adult population.